ASSEMBLY LINE WORKERS OF THE 21st CENTURY: A Glimpse Into the Lives of Customer Service Center Agents - Hega, Mylene D. (Philippine Journal of Social Development; 2007, 2010)
This article takes a broad view of the phenomenon of customer service centers which have emerged as a distinctive aspect of the globalized economy. The rapid growth in call centers is a result of transnational economic processes that take place in terrains made uneven by differences in economic development across countries. Using data from a number of sources, including focus group discussions and individual interviews, the author  looks at the lives of Philippine call center employees with a lens that highlights gender and other oppressions.  She also discusses what actions can be taken to protect workers’ rights. Lastly, the author problematizes the new conditions for labor organizing among customer service center agents.